COMPARISON OF THE PREVALENCE AND DYNAMICS OF ANXIETY, DEPRESSION AND QUALITY OF LIFE IN PATIENTS WITH CHRONIC RHEUMATIC HEART DISEASE - V. S. Petrov (SINAPS LLC, 2019)
The objective. The assessment of the severity, prevalence and five-year dynamics of anxiety and depression in those studied with rheumatic heart disease.Materials and methods. The study included 168 patients with rheumatic heart disease: mean age 58,69±0,47 years; 141 women (83,93%) and 27 men (16,07%). To assess anxiety and depression, the following scales were used: HADS (hospital anxiety and depression scale), CES-D (depression scale of the epidemiological research center), and STAI (Spielberger anxiety scale). Quality of life was assessed using total scale SF-36 (Short Form Medical Outcomes Study), KCCQ (Kansas questionnaire for patients with cardiomyopathy), and MHFLQ (Minnesota questionnaire for the quality of life of patients with CHF).Results. Initially, patients with rheumatic heart disease had mild depression and anxiety, except for the high level of state anxiety according to STAI - 48.00 ± 0.95. More pronounced depressive disorders were revealed in patients with CHF NYHA III and IV. According to CES-D - 17,58±1,27 for FC I and 23,4±0,75 for FC IV, for HADS - 7,00±0,64 for FC I and 13,6±0,78 for FC IV. Anxiety disorders, on the contrary, were less with III and IV FC CHF: 8,5±0,49 with FC I and 8,2±1,02 with FC IV in HADS. According to STAI state anxiety - 47,58±1,22 (FC I) and 42,8±1,76 (FC IV), for trait anxiety - 42,67±1,08 (FC I) and 40,4±1,85 (FC IV). For the five-year period there was no negative and positive dynamics according to the questionnaires of anxiety and depression. The only exception was the increase in anxiety according to HADS by 0.66 points. In terms of quality of life, there was a decrease in physical health according to SF-36 by 1.78, and in overall summary score according to KCCQ by 1.55 and MHFLQ by - 3.99.Conclusions. In patients with rheumatic heart disease, the severity of anxiety and depression is insignificant and does not increase during five years of observation. Indicators of depression are more pronounced in the group with CHF NYHA III and IV, and anxiety indicators in patients with CHF NYHA I and II. An increase in depression rates in subjects with rheumatic heart disease is associated with a deterioration in the quality of life. With an improvement in the quality of life values, depressive symptoms decrease, and anxiety rates increase.